Hugo Pratt and Milo Manara’s Indian Summer: An Italian “Source” for The Scarlet Letter - Mariani, Giorgio (Review of International American Studies, 2017)
Giorgio Mariani Università “Sapienza” di Roma Italy Hugo Pratt’s and Milo Manara’s Indian Summer: An Italian “Source” for The Scarlet Letter This paper examines the allusions of Milo Manara’s and Hugo Pratt’s graphic novel, Tutto ricominciò con un’estate indiana (Indian Summer), to Hawthorne’s novel The Scarlett Letter in a variety of ways. In particular, this paper argues that not only some of Pratt and Manara’s characters are very liberal, creative reinventions of Hawthorne’s figures—they might be seen as “spin-offs” of Hawthorne’s narrative—but in many ways Indian Summer is also thematically close to The Scarlet Letter.